Pengaruh Kualitas Pendidkan Terhadap Tingkat Pengangguran di Pulau Jawa: The Leverage of Education Quality on the Unemployment Rate in Java Island - Dini Riya, Aceu Nur; Wahyu Ismail , Andika; Heldayanti, Lidia (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2024)
The objective of this research is to comprehend how the quality of education effect the unemployment rate specifically on the island of Java. The choice of the research subject is regarded as the focal point of educational centers in Indonesia. The employed variables encompass the unemployment rate as the dependent variable and school years expectancy, literacy rate and net enrollment rate as independent variables. The research employed is of a descriptive nature utilizing a quantitative approach, and the methodology applied is Ordinary Least Squares (OLS). This study utilizes secondary data sourced from the Central Bureau of Statistics. The research employs panel data spanning from 2015 to 2022. Views 12 software is used as an analysis tool. In the t-test results, the study indicated a significant impact of the unemployment rate based on expected years of schooling and literacy rates, whereas the net enrollment rate did not exhibit a significant influence on the unemployment rate. While the F test shows that all variables have a significant positive effect on the unemployment rate.